Developing protein arginine methyltransferase 1 (PRMT1) inhibitor TC-E-5003 as an antitumor drug using INEI drug delivery systems. (1st January 2020) - Zhang, Pengcheng; Tao, He; Yu, Liyang; Zhou, Lixiao; Zhu, Chenggang
Abstract: Injectable implants with the ability to form in situ are one of the most promising carriers for the delivery of chemotherapeutic drugs to tumor sites. We have reported a novel injectable in situ-forming implant system composed of n-butyl-2-cyanoacrylate (NBCA), ethyl oleate, along with the sol-gel phase transition. The chemotherapeutic drug-loaded injectable NBCA ethyl oleate implant (INEI) exhibited excellent therapeutic efficacy for local chemotherapy. Herein, we utilize this INEI to carry N, N′-(Sulfonyldi-4, 1-phenylene)bis(2-chloroacetamide) (TE-C-5003), which is a selective protein arginine methyltransferase 1 (PRMT1) inhibitor, to treat the lung cancer mice model. The in vitro experiment shows that TE-C-5003 has a good anti-tumor effect on lung cancer (IC50 = 0.7022 µM for A549; IC50 = 0.6844 µM for NCL-H1299) and breast cancer (IC50 = 0.4128 µM for MCF-7; IC50 = 0.5965 µM for MDA-MB-231). Anti-tumor experiments in animal models showed that the average growth inhibition rate of xenografted human lung cancer cells by the TE-C-5003-loaded INEI (40% NBCA) was 68.23%, which is far more than TC-E-5003 alone (31.76%). Our study further confirms that INEI is an effective technique to improve the anti-tumor effect. The druggability of small molecule compounds can be improved with the help of the mentioned technology. Also, TC-E-5003 may be developed as a broad spectrum anti-tumor drug.